PPPDM – a privacy-preserving platform for data mashup. (1st January 2012) - Barhamgi, Mahmoud; Benslimane, Djamal; Ghedira, Chirine; Benharkat, Aïcha-Nabila; Gancarski, Alda Lopes
Data mashup is an important class of the situational applications that combines information on the fly from multiple data sources to respond to immediate business data needs. Mashing-up data requires important programming skills on the side of mashups' creators, and involves handling many challenging privacy and security concerns raised by data providers. In this paper, we propose a declarative approach for mashing-up data. The approach allows the mashups' creators to create data mashups without any programming involved, they just need to specify 'declaratively' their data needs. The approach exploits the mature query rewriting techniques to build the mashups automatically while taking into account the data's privacy and security concerns. We apply the proposed approach to the healthcare domain, and report a thorough experimental evaluation. The reported results are very promising.